2010
DOI: 10.1016/j.pain.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8, but not TRPA1, is required for neural and behavioral responses to acute noxious cold temperatures and cold-mimetics in vivo

Abstract: Somatosensory neurons detect environmental stimuli, converting external cues into neural activity that is relayed first to second-order neurons in the spinal cord. The detection of cold is proposed to be mediated by the ion channels TRPM8 and TRPA1. However, there is significant debate regarding the role of each channel in cold-evoked pain, complicating their potential as drug targets for conditions such as cold allodynia and hyperalgesia. To address this debate, we generated mice lacking functional copies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
232
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(246 citation statements)
references
References 56 publications
(122 reference statements)
12
232
2
Order By: Relevance
“…Mammalian TRPA1 has been suggested to function as a cold-activated channel (41,42); thus, one could argue that we have interchanged properties between two thermally sensitive channel orthologs, albeit in opposite directions (cold-sensitive vs. heat-sensitive). However, under our experimental conditions, oocytes expressing human TRPA1 showed no cold-evoked currents with cooling down to 10-12°C, consistent with recent reports that cold produces slight or no activation of transfected cells or sensory neurons expressing TRPA1 (43,44). Aminoterminal ARs represent a structural hallmark of many members of the extended family of TRP channels, but their functional roles remain largely unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Mammalian TRPA1 has been suggested to function as a cold-activated channel (41,42); thus, one could argue that we have interchanged properties between two thermally sensitive channel orthologs, albeit in opposite directions (cold-sensitive vs. heat-sensitive). However, under our experimental conditions, oocytes expressing human TRPA1 showed no cold-evoked currents with cooling down to 10-12°C, consistent with recent reports that cold produces slight or no activation of transfected cells or sensory neurons expressing TRPA1 (43,44). Aminoterminal ARs represent a structural hallmark of many members of the extended family of TRP channels, but their functional roles remain largely unknown.…”
Section: Discussionsupporting
confidence: 91%
“…As it will be presented in the next paragraph, the currently proposed key role of TRPM8 in both noxious and non-noxious cold transduction (182,183) follows what it has been a controversial debate on the potential role of ion channels other than TRPM8 (e.g. TRPA1) (279) in selectively gating noxious cold temperatures (47).…”
Section: Non-noxious Cold Transductionmentioning
confidence: 85%
“…Specifically, selectively ablating TRPM8-expressing neurons in vivo resulted in mice: 1) being insensitive to both innocuous and noxious cold; 2) showing attenuated cold hypersensitivity after injury; 3) displaying a loss of cold analgesia after injury; 4) showing normal heat sensation, mechanosensation, and proprioception (182,183). Altogether, such findings have led to the recent view that TRPM8-expressing neurons could therefore represent a broad labelled line for cold detection in mammals and that, due to its role in mediating noxious cold temperatures, the TRPM8 ion channel could in fact have a general role in cold detection over a wide range of temperatures (down to 5°C) (182,183).…”
Section: Non-noxious Cold Transductionmentioning
confidence: 99%
“…Several studies demonstrated that noxious cold activates TRPA1 channels, both directly [118][119][120] and indirectly [121]. However, negative results were obtained in mouse TRPA1 channels heterologously expressed in human embryonic kidney cells [122], and neuronal activation by cold temperatures was found to be similar between wild-type and TRPA1 knock-out mice [123]. In addition, in vivo studies employing two independently produced TRPA1 knock-out mice breeds yield conflicting results, leaving the controversy unsettled [115,117,120].…”
Section: Trpa1mentioning
confidence: 99%